One-step loop-mediated isothermal amplification system for Mycobacterium marinum detection - Kayo Okumura; Yuji Miyamoto; Satoshi Mitarai; Manabu Ato (Microbiology Spectrum, 2025)
ABSTRACT Mycobacterium marinum is the etiological agent of cutaneous nontuberculous mycobacteriosis, inducing granuloma formation in human skin. Other mycobacterial species, including Mycobacterium ulcerans, Mycobacterium chelonae, and Mycobacterium fortuitum, also cause cutaneous infections, with M. ulcerans and M. ulcerans subsp. shinshuense showing close genetic relatedness to M. marinum. M. ulcerans is a recognized causative agent of Buruli ulcer, and numerous molecular detection and diagnostic methods have been established. However, there is a lack of specific detection methods for M. marinum. Currently, confirming M. marinum infection requires 16S rRNA or housekeeping gene sequencing, which is labor-intensive and time-consuming. In this study, we developed a one-step colorimetric loop-mediated isothermal amplification assay for simple and specific detection of M. marinum. The results were confirmed by visual inspection of color change in the reaction solution, eliminating the need for specialized equipment. Our proposed workflow can be completed within 60 minutes from sample preparation to detection with high sensitivity. To the best of our knowledge, the loop-mediated isothermal amplification assay developed in this study represents the only test capable of specifically detecting M. marinum utilizing only the loop-mediated isothermal amplification reaction. Consequently, this loop-mediated isothermal amplification assay has the potential for implementation in routine diagnosis of M. marinum.IMPORTANCEMycobacterium marinum and Mycobacterium ulcerans, which are frequently reported as etiological agents of cutaneous nontuberculous mycobacteria, exhibit similar characteristics in terms of symptomatology and patient demographics. However, there is currently no simple identification method to distinguish between these two species. The one-step loop-mediated isothermal amplification method developed in this study represents a rapid diagnostic approach that yields results in a short time frame and does not necessitate specialized precision instruments, as the results can be visually determined. Consequently, the loop-mediated isothermal amplification method established in this study is anticipated to contribute significantly to the advancement of diagnostic techniques for cutaneous nontuberculous mycobacteria.